Keragaman Makro Alga Berdasarkan Karakter Morfologis Di Pantai Ria Kecamatan Woja Kabupaten Dompu - Leni Maulani Puja; Nikman Azmin; Ariyansyah (JUSTER : Jurnal Sains dan Terapan, 2024)
sea. This study aims to find out the types of macroalgae found in Ria Beach, Woja District, Dompu Regency, to find out the Macro Diversity of algae in Ria Beach, Woja District, Dompu Regency. This study used an exploratory survey method, sampling using the Transect Line method with the Quadrant Sampling technique. Analysis of data types and utilization of research results using qualitative analysis techniques, while the level of diversity using quantitative analysis techniques, namely the index of diversity. The results of the study in the Ria Beach area, Woja District, Dompu Regency found 4 types of macroalgae, namely, Boergesenia forbesii, Ulva lactuta, Padina australis, Sargassum polycystum. The diversity of macroalgae species in the Ria Beach area, Woja District, Dompu Regency is moderate.